Estimating entrepreneurial risk in Russian small and medium-sized enterprises - Pinkovetskaia, Iuliia S.; Sverdlikova, Elena A.; Lebedev, Anton V. (The journal of contemporary issues in business and government, 2019)
Identifying risks is essential to ensure the efficiency of activities of small and medium-sized enterprises who are most exposed to the effects of risks due to limited resources and their structural features. The purpose of this study was to define the levels of entrepreneurial risk prevailing in recent years in Russian micro, small and medium-sized enterprises. The study used data from the official statistical collection of activities of all Russian enterprises for the period 2015 to 2017, representing 82 Russian regions and thirteen types of economic activity. The highest level of acceptable entrepreneurial risk was observed in the trade industry. The highest level of critical entrepreneurial risk was observed in enterprises specializing in the production and distribution of electricity, gas and water, and in mining. The highest level of catastrophic risk was observed in enterprises specializing in building and construction, transport and communications, and in wholesale and retail trade. These results could be of interest to entrepreneurs when choosing the type of sectors to engage in, and to policymakers in supporting enterprises in particular economic sectors of Russia. This paper aims to contribute to the scholarly debate on the establishment of levels of entrepreneurial risk.